COMPUTER MODULE OF THE PROGRAM FOR DETERMINING THE OPTIMUM FORM OF THREAD FILING ON TECHNOLOGICAL EQUIPMENT - SHCHERBAN, VOLODYMY; KOLVA , NIKITA; EGOROV, DMITRIJ; SHILINGOV, SERGEY; LUKASHEV, ANDREW (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The results of determining the optimal form of thread filling on the technological equipment of the light and textile industry using the computer module of the program for determining the tension of technological processes are given. The computer module of the program for determining the intensity of technological processes, using the recursion algorithm, allows you to determine the optimal form of filling the thread for obstacles in the form of a vertical straight line, a circle and a rectangle. These geometric images reflect real guides and working bodies of technological equipment. The development of new technological processes in the light and textile industries and the improvement of existing ones is based on the optimization of thread tension in the working area. An increase in the amount of tension leads to thread breaks, and a decrease in its value leads to a violation of technological processes, a deterioration in the quality of manufactured products and, as a result, also leads to breaks in raw materials. Thus, the optimization of the thread tension in the working area allows you to maximally exclude thread breaks, increase the productivity of the technological equipment and the quality of the manufactured products. When processing raw materials on the technological equipment of the light and textile industry, the thread tension gradually increases from the exit zone from the packaging to the working zone. The increase in tension is due to the contact of the thread with the guiding and working bodies of the technological equipment of the light and textile industry. Due to the frictional forces in the contact zone, the thread tension increases after the guiding and working bodies of the technological equipment. The magnitude of the friction force is affected by the angle of coverage of the thread of the guide. The form of filling the thread on the technological equipment is a broken line. The guiding and working bodies of the technological equipment are located at the breaking points. Optimizing the filling form consists in minimizing the total angle of coverage of the guide thread. Graph theory and specialized software must be used to solve the complex task of optimizing the thread filling form on technological equipment. The magnitude of the frictional force in the zone of contact with the guiding and working bodies of the technological equipment of the light and textile industry depends on the tension of the thread in front of the guide, the radius of curvature of the guide surface, the angle of coverage by the thread of the guide, guide material and thread, speed of thread movement.